The Book of Repetition: Rachel Cusk and Maternal Subjectivity - Clare HANSON (E-REA)
This essay discusses Cusk’s representation of maternal subjectivity in the context of an Anglo-American post-feminist culture which construes motherhood simultaneously as an individual choice and a social responsibility. It argues that what is distinctive about Cusk’s writing on motherhood is her focus first on the disjunctions between subjective experience and public discourses of motherhood and secondly on the fissures within maternal subjectivity which are, in part, a consequence of this disjunction. This essay explores her treatment of these themes with reference to popular discourses of motherhood and the psychoanalytic perspectives which are both invoked and critiqued in her work.